Open-wedge high tibial osteotomy in patients with discoid lateral meniscus. (10th June 2021) - Kim, Hee-June; Shin, Ji-Yeon; Lee, Hyun-Joo; Jung, Chul-Hee; Park, Kyeong-Hyeon; Oh, Chang-Wug; Kyung, Hee-Soo
Background: There are concerns about the progression of the lateral osteoarthritis (OA) should be taken into account when high tibial osteotomy (HTO) is performed in patients with discoid lateral meniscus (LM). This study evaluated the clinical results of HTO in patients with discoid LM and elucidated factors affecting the results. Methods: This study evaluated 32 female patients with varus deformity and medial OA. Patients with discoid LM (8 patients) or without discoid LM (24 patients) underwent open-wedge HTO. The mean age was 53.5 years and the mean follow-up period was 35 months. Clinical results, including the Hospital for Special Surgery (HSS) score, Knee Society knee score (KS) and function score (FS), were evaluated. The progression of OA in the lateral compartment was also evaluated. Finally, we evaluated the factors affecting the clinical results and OA progression in the lateral compartment. Results: Between two groups, all clinical scores were not different (p = 0.964, 0.963, and 0.559, respectively). Three of eight patients (37.5%) in the discoid group developed OA in the lateral compartment, whereas 2 of 24 patients (8.3%) in the control group developed such; however, this was not significantly different (p = 0.085). In discoid group, patients with undercorrection has higher KS relative to patients with acceptable correction (p = 0.044). Other clinical results and OA change in the lateral compartment were not affected by evaluated factors. Conclusions: Patients who underwent open-wedge HTO showed the satisfactory clinical results and lateral OA progression regardless of the presence or absence discoid LM. However, when discoid LM was present, patients with undercorrection showed higher KS in comparison with patients with acceptable correction.